2011
DOI: 10.1093/jxb/err133
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of elevated CO2, warming, and drought on photosynthesis of Deschampsia flexuosa in a temperate heath ecosystem

Abstract: Global change factors affect plant carbon uptake in concert. In order to investigate the response directions and potential interactive effects, and to understand the underlying mechanisms, multifactor experiments are needed. The focus of this study was on the photosynthetic response to elevated CO2 [CO2; free air CO2 enrichment (FACE)], drought (D; water-excluding curtains), and night-time warming (T; infrared-reflective curtains) in a temperate heath. A/Ci curves were measured, allowing analysis of light-satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 60 publications
2
53
2
Order By: Relevance
“…Also the dry weight of the rosettes was significantly lower in the low CO 2 condition ( Figure 1B ). In contrast, there were no effects on rosette growth under high CO 2 conditions, which was rather unexpected since most previous studies have reported an increase in biomass (Bowes, 1991; Leakey et al, 2009). However, our experimental conditions may not have been optimal for stimulated growth by elevated CO 2 (Temme et al, 2015) and moreover, the Col-0 accession that we used may respond differently to high CO 2 than other plant species (Li et al, 2006; Leakey et al, 2009; Temme et al, 2015).…”
Section: Resultsmentioning
confidence: 50%
“…Also the dry weight of the rosettes was significantly lower in the low CO 2 condition ( Figure 1B ). In contrast, there were no effects on rosette growth under high CO 2 conditions, which was rather unexpected since most previous studies have reported an increase in biomass (Bowes, 1991; Leakey et al, 2009). However, our experimental conditions may not have been optimal for stimulated growth by elevated CO 2 (Temme et al, 2015) and moreover, the Col-0 accession that we used may respond differently to high CO 2 than other plant species (Li et al, 2006; Leakey et al, 2009; Temme et al, 2015).…”
Section: Resultsmentioning
confidence: 50%
“…In the CLIMAITE experiment, Albert et al (2011aAlbert et al ( , 2011b found increased net photosynthesis and increased leaf C : N ratios in response to elevated CO 2. This is comparable to our higher root C : N ratio, which supports our hypothesis of the improved carbon status of the plant and a higher C allocation to roots grown under elevated CO 2 .…”
Section: Net Root Growth and Standing Root Biomassmentioning
confidence: 95%
“…We hypothesised that root growth would be stimulated in response to elevated CO 2 due to increased C uptake (Albert et al 2011a;Albert et al 2011b), and that therefore there would be greater C allocation to the roots. Drought was expected to slow down root growth, whereas the temperature treatment was expected to increase root growth, depending on soil moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies about the effect of experimental warming on tree species have focused primarily on net mineralization, net nitrification and denitrification rates, ectomycorrhizal colonization and root exudation in early growing season, peak of growing season and non-growing season (Zhao and Liu, 2009;Yin et al, 2012Yin et al, , 2013Yin et al, , 2014. Global warming affects plant growth through direct effects on photosynthesis and respiration (Albert et al, 2011) and indirect effects on soil nitrogen availability (Sardans et al, 2008) and soil moisture (Holsten et al, 2009). Previous study reported that an increase in autumn temperature did not increase the photosynthetic rate but affects the consumption of excess energy in seedlings of Jack pine (Busch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%